Intellectual Capital, Corporate Social Responsibility, and Firm Value in Indonesia's Banking Industries - Geby Agnes LumbanGaol; Amrie Firmansyah; Ayu Diana Irawati (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This study investigates the effect of intellectual capital and corporate social responsibility on the firm value in Indonesia Banking companies. This study was designed as a quantitative study based on multiple linear regression models. The study sample of 116 observations was selected from banking companies listed on the Indonesia Stock Exchange that met the criteria for having financial reports with complete data and disclosing corporate social responsibility in the 2014-2019 period. Research finds that intellectual capital has a positive and significant effect on firm value. On the other hand, corporate social responsibility does not affect firm value. The banking companies must manage intellectual because it positively impacts the market better and efficiently. Also, corporate social responsibility activities need to be improved to obtain a more positive response from the market.